THE EVALUATION OF COMPUTER-BASED NATIONAL EXAMINATION SYSTEM IN INDONESIA - Handoko, Handoko; Tolla, Burhannudin; Suprihati, Yetti (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
Benchmarks of educational success can be seen from the achievement of student learning outcomes through national examinations held by the government at least once in the education level unit: SMA, SMK, and MA here, since 2014, the government has changed the pen and paper-based national examinations to become computer-based national examinations. The system is implemented semi-online which means the questions are sent online and students work on the problems manually via the school computer off-line. Changes to the examination system must be accompanied by adequate and professional human resources as implementers and information technology systems. This research was carried out by taking a sample of 7 schools (high schools, vocational schools, and MA), all of which are in Jakarta. The research method is qualitatively using observation and interviews. The design of the research design is a combination of two research models namely CIPP and Kirkpatrick. The results of the study show that computer-based exams have more advantages compared to paper-based exams in terms of the distribution of questions and answers, time for examining results, and reducing paper usage. Keyword: National Examination, computer-based National Examination, Paper-based test, and Student Learning Outcomes